Experimentation and Analysis Routing Stability in Mobile Ad Hoc Network - Hala KHANKHOUR1; Otman ABDOUN2; Jaafar ABOUCHABAKA1 (Communications of International Proceedings, 2021)
Mobile multi-user wireless Ad Hoc networks have attracted the attention of the scientific community for several years. Wireless networks can be classified into two types: infrastructure-based wireless networks and infrastructure-less (ad hoc) wireless networks. In this survey paper, we focus on the mobile Ad Hoc network. Network performance depends on the routing protocol which has a vital role in spreading the message among the moving vehicles and in some research revealing on real scenarios they have obtained optimum values of the network quality of service. To solve this kind of routing problem in the Ad Hoc network, this paper presents a performance comparison between two variables of protocols, to reduce the control overheads such as route query packets as well as the flooding time for collecting the network topology information at a destination. The first, reactive, is called AODV (Ad Hoc On-demand Distance Vector Routing). It uses a broadcast mechanism in the network to discover valid routes. The second is proactive and is called OLSR (Optimized Link State Routing Protocol). It uses a mechanism that makes it possible to designate a subset of its neighborhood responsible for the dissemination of topology control information in networks at a lower cost. Thus, the comparison of these two protocol results at the level of the quality of service will help the user subsequently to select a particular routing protocol suitable for Ad Hoc vehicular Networks.
Keywords: AODV; OLSR; NS-3; Ad Hoc.